Place-name of Brahmonbaria District: An introductory linguistic study - Ara, Gulshan (Dhaka University Journal of Linguistics, 2010)
Although place-names are strictly defined as geographical names but they may be derived from diverse linguistic roots and they form part of the cultural and linguistic history of the country. Hence, Bengali place-name has been an interesting area of Bengali Linguistics explored by different language researchers and linguists at different times. In this present study, `the place names of Brahmanbaria: linguistic perspectives' aims at achieving the diverse linguistic analysis of morphemic structures as well as phonetic changes in the regional or dialectal utterances of the collected place-names. The study also aims at creating new interest in the field of place-name analysis to the new researchers as well. Key words: Place-Name, Compound word, affixes DOI: 10.3329/dujl.v2i3.4146 The Dhaka University Journal of Linguistics: Vol.2 No.3 February, 2009 Page: 101-110